Hemorrhagic Shock Sensitized the Diaphragm to Ventilator-Induced Dysfunction through the Activation of IL-6/JAK/STAT Signaling-Mediated Autophagy in Rats - Zhang, Li-Juan; Ni, Shao-Zhou; Zhou, Xian-Long; Zhao, Yan (Mediators of Inflammation, 2019)
Mechanical ventilation (MV) is a major life support technique for the management of trauma-associated hemorrhagic shock (HS). Ventilator-induced diaphragm dysfunction (VIDD), one of the most common complications of MV, has been well demonstrated in animal and human studies. However, few data are available concerning the effects of MV on diaphragm function in HS victims. In the present study, we found diaphragm muscle atrophy and weakness in HS but not in healthy animals after 4 hours of MV. The inhibition of autophagy resulted in reduced muscle fiber atrophy and improved forces. In addition, we observed diaphragmatic interleukin- (IL-) 6 overexpression and activation of its downstream signaling JAK/STAT in HS animals after MV, and either the neutralization of IL-6 or the inhibition of the JAK/STAT pathway attenuated autophagy, diaphragm atrophy, and weakness. Importantly, treatment with nonselective antioxidant exerted no protective effects against VIDD in HS animals. In addition, in vitro study showed that exogenous IL-6 was able to induce activation of JAK/STAT signaling and to increase autophagy in C2C12 cells. Moreover, the inhibition of JAK/STAT signaling abolished IL-6-induced cell autophagy. Together, our results suggested that HS sensitized the diaphragm to ventilator-induced atrophy and weakness through the activation of IL-6/JAK/STAT signaling-mediated autophagy in rats.